Neurotheology and Theology: Introductory Issues - Grygiel, Alicja; Owczarek, Katarzyna; Patelska, Weronika; Romaniuk, Franciszek; Rybicka, Patrycja; Strzyżyński, Przemysław; Woźny , Michał (Filozofia Chrześcijańska, 2025)
The article presents neurotheology as an interdisciplinary field studying the relationship between religious experiences and brain activity. It discusses its methodology, history, and key researchers. The relationship between neurotheology and theology is analyzed, along with critical perspectives on its assumptions. Potential directions for the field’s development are outlined. The article also presents the scope of cooperation between theology and neurotheology, as well as the potential benefits of this collaboration for the former field.